2022
DOI: 10.1111/jgs.17723
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for discussing long‐term prognosis when deciding on cancer screening for adults over age 75

Abstract: Background: Consideration of older adults' 10-year prognosis is necessary for high-quality cancer screening decisions. However, few primary care providers (PCPs) discuss long-term (10-year) prognosis with older adults.Methods: To learn PCPs' and older adults' perspectives on and to develop strategies for discussing long-term prognosis in the context of cancer screening decisions, we conducted qualitative individual interviews with adults 76-89 and focus groups or individual interviews with PCPs. We recruited p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…With regard to timing of prognostic information, patients especially perceived harm when prognostic information was discussed too early 25,44,45,55,60–65 . This could cause anxiety and take away hope, which some patients so desperately need to stay upright mentally and physically.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to timing of prognostic information, patients especially perceived harm when prognostic information was discussed too early 25,44,45,55,60–65 . This could cause anxiety and take away hope, which some patients so desperately need to stay upright mentally and physically.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to timing of prognostic information, patients especially perceived harm when prognostic information was discussed too early. 25,44,45,55,[60][61][62][63][64][65] This could cause anxiety and take away hope, which some patients so desperately need to stay upright mentally and physically. In contrast, caregivers reported that it is harmful when prognostic information is discussed too late (too close to death) 66,67 as it takes away the time to say goodbye to a loved one.…”
Section: Prognostic Information Provision Could Be Harmful When Timin...mentioning
confidence: 99%
See 1 more Smart Citation